INTERPRETATION OF SPECTRAL DECOMPOSITION IN RESERVOIR CHARACTERIZATION USING SHORT TIME FOURIER TRANSFORM AND CONTINUOUS WAVELET TRANSFORM - Ulum K. I. Yusrie (NIM 22305005), Bahrul
ABSTRACT: Spectral decomposition is an important signal anlysis tool for interpretation in seismic data. Spectral decomposition is used for imaging and mapping temporal bed thickness and discontinuities over 3D surveys. This technology can improve your prospect definition by using continuous wavelet transform (CWT) which resolution is better in signal anlysis. Traditionally, 2D representation in time and frequency space for 1D signal is achieved by taking the fourier transform over a short time window. This method is commonly known as Short Time Fourier Transform (STFT). But time frequency resolution in STFT is limited by the choice of a window length. The windowing problem in time frequency is absent in Continuous Wavelet Transform (CWT) method. The limitation of STFT method can be overcome by CWT method using wavelet for signal anlysis in time frequency that time frequency resolution is better. Wavelet basis function with compact support having the property of dilation and translation provide us the mechanism to perform such analysis. Frequency resolution obtained by dilating wavelet used fixed scale and time resolution obtained by translating wavelet with fixed translation factor. This methodology made continuous wavelet transform (CWT) produce better resolution in signal anlysis.